Halite formations of Canada for clean energy storage (hydrogen, CAES): A geologic review - Pavel Kabanov; Nicolas Pinet; Frank Brunton; Omid Haeri Ardakani; Christine Deblonde; Keith Dewing; Peter Giles; Paul Durling; Marty Henning; Nicholas Utting (Earth-Science Reviews, 2026)

Revealing Yukon’s hidden treasure: an atomic-scale investigation of Carlin-type gold mineralization in the Nadaleen Trend, Canada - Phillip Gopon; Patrick Sack; Nicolas Pinet; James O. Douglas; Benjamin M. Jenkins; Brooke Johnson; Ella Penny; Michael P. Moody; Laurence Robb (Mineralium Deposita, 2025)
The invisible-gold deposits known as Carlin-type are becoming more important as easier to find deposits are progressively depleted. The combination of the invisible nature of the Au in these deposits, as well as the limited surface indicators of these deposits, makes exploration to find new Carlin-type deposits extremely difficult. Comprehensive mineralization models are essential to find new Carlin-type deposits in similar geologic settings. The Nadaleen Trend of Yukon, Canada, is one such district where an improved understanding of this deposit type has led to new discoveries. Previous studies compared and contrasted the tectonic setting, host rock depositional setting, structural preparation, and mineralization style of the Nadaleen Trend with those in Carlin-type localities, Nevada. However, the comparisons at an atomic scale, between Carlin-type Au deposits in the Nadaleen Trend and those in Nevada, has yet to be investigated. This study fills this knowledge gap by combining high resolution microanalytical techniques with atom probe tomography to examine the distribution of Au and other trace elements in the Nadaleen Trend, compare them to a representative Carlin-type deposit in Nevada (Turquoise Ridge), and determine how widespread the mineralization model is. Our findings show that in the Nadaleen Trend, as in Nevada, Au is generally directly linked with As at the macro to atomic scale, and is incorporated into As/Au rich overgrowths on sedimentary/diagenetic pyrite. Gold-rich pyrite rims in the Nadaleen Trend are generally smaller than those found in Nevada (0.5–2 µm vs > 10 µm), although the ore grades appear comparable. We find that the Au in the pyrite of the Nadaleen Trend is homogenously distributed (i.e. lattice bound) at the atomic scale, but that there is a notable enrichment of As surrounding individual Au atoms. These findings are in agreement with those from previous work on a representative deposit in Nevada, and support the assertation that As is the key ingredient in facilitating the incorporation of Au into the pyrite lattice. Arsenic as an essential component in the trapping mechanisms of Au in CTG deposits, is something that has been as to yet underappreciated in the current models of CTG deposit formation.

A fresh look at the Gulf of St. Lawrence, Eastern Canada: Geophysical imaging of salt bodies and volcanic rocks in the upper Paleozoic Magdalen Basin - Nicolas Pinet; Virginia Brake (Marine and Petroleum Geology, 2024)

Thermal history of Carlin-type gold deposits in Yukon (Canada) as revealed by organic matter geothermometry, clumped isotope data, fluid inclusion microthermometry, and apatite fission-track analyses - Nicolas Pinet; Omid Haeri-Ardakani; Josué Jautzy; Martine M. Savard; Patrick Sack; Patrick Mercier-Langevin (Mineralium Deposita, 2023)
Sediment-hosted gold deposits in central Yukon have most of the diagnostic characteristics of Carlin-type gold deposits in Nevada. This study combines organic matter geothermometry with fluid inclusion microthermometry, clumped isotope data (Δ 47 ) for late ore-stage hydrothermal calcite, and apatite fission-track analyses to constrain the thermal evolution of Carlin-type gold zones in central Yukon. The Tmax parameter derived from pyrolysis analyses indicates that organic matter is overmature and records regional temperatures of > 150 °C. Calcite and fluorite associated with the waning stage of mineralization at ca. 74 Ma have mean fluid inclusion homogenization temperatures of 123–173 °C, with an average salinity of 4.8 wt.% NaCl equiv. These temperatures overlap values of 91–162 °C determined from calcite clumped isotope measurements and are similar to data from Carlin-type deposits in Nevada. Fluid mixing is suggested by a variation of the isotopic composition of the fluid in equilibrium with calcite, with the higher temperature end-member having higher δ 18 O H2O values. In thermal models based on Tmax, fluid inclusion microthermometry, clumped isotope measurements, and apatite fission-track data, a higher temperature event at approximately 220 °C is consistent with pyrobitumen reflectance measurements. This event is either related to maximum tectonic burial prior to mineralization or to the flow of acidic hydrothermal fluids early in the main ore-stage. Each analytical technique used in this study is independent of the others and records part of the thermal and chemical evolution of the Yukon Carlin-type gold deposits and their host rocks.

Regional significance of normal fault systems in the western Canadian Beaufort Sea (Mackenzie delta) - Nicolas Pinet; Virginia Brake; Mathieu J. Duchesne (Tectonophysics, 2023)

Linking a linear pockmark train with a buried Palaeozoic structure: a case study from the St. Lawrence Estuary - Nicolas Pinet; Mathieu Duchesne; Denis Lavoie (Geo-Marine Letters, 2010)